Natural product based approaches to overcome Candida glabrata and emerging AMR threats - Sahu, Binaya Krushna; Patra, Sudipta Kumar; Sahu, Mahesh Chandra; Panda, Sujogya Kumar (Frontiers in Antibiotics, 2026)
The rise of C. glabrata as a serious, multidrug-resistant organism poses a significant and global challenge to the human health. The reasons C. glabrata has developed resistance to standard antifungal drugs, include the activation of efflux pumps, the production of biofilms, and changes in ergosterol biosynthesis. In light of the threat posed by C. glabrata, the potential of phytochemicals as therapeutic alternatives should be considered due to their diverse structures and ability to exhibit more than one type of antifungal activity. This review summarizes advances in the use of plant-based natural products displaying antifungal activity against C. glabrata, with an emphasis on key classes of phytochemicals, including flavonoids, terpenoids, phenolic compounds, alkaloids, and essential oils. While the proposed mechanisms include disruption of cell membranes, inhibition of ergosterol synthesis, attenuation of oxidative stress, and suppression of virulence and biofilm formation, it is important to note that most evidence arises from in vitro studies, with only limited mechanistic investigations on individual compounds. Although in vitro studies indicate promising antifungal and adjunctive effects, the available evidence remains largely preclinical, with variable synergistic outcomes. Such synergy not only enhances therapeutic efficacy but also reduces required drug dosages, thereby minimizing toxicity and delaying the emergence of resistance. Major limitations include inconsistency in phytochemical composition, insufficient pharmacokinetic data, and a lack of robust in vivo and clinical studies. This review critically integrates current knowledge, highlighting both the multi-target potential of phytochemicals against C. glabrata and the key challenges that must be addressed to enable realistic clinical translation. By prioritizing synergy-focused research, and methodological standardization, phytocompounds can be positioned not merely as standalone agents but as adjunctive modulators of antifungal resistance, paving the way for novel, effective, and sustainable therapeutic options against MDR C. glabrata.